STRATEGIC METHODOLOGY FOR TEACHING ONOMASTIC UNITS IN ENGLISH AND UZBEK LANGUAGES BASED ON A LINGUOCULTUROLOGICAL APPROACH - Mamatkulova Bakhtijon Ravshanovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines strategic methodology for teaching onomastic units in English and Uzbek languages through a linguoculturological approach. The study  highlights  the  importance  of  proper  names  (anthroponyms,  toponyms, ethnonyms) as carriers of cultural and historical information. A strategic integration of linguistic and cultural components is proposed to enhance learners’ communicative and intercultural competence. The research emphasizes modern pedagogical strategies such as contextual learning, comparative analysis, and culturally oriented tasks. The findings  suggest  that  a  strategic  approach  to  teaching  onomastics  fosters  deeper understanding  of  national  identity,  cultural  values,  and  language  usage  in  real communicative contexts.